Rare Occurrence of Inhibitors in Von Willebrand Disease: A Case Report - Kulkarni, Bipin P.; Ghargi, Kirti; Shanmukhaiah, Chandrakala; Shetty, Shrimati D. (Frontiers in Medicine, 2022)
Introduction: Type 3 Von Willebrand Disease (VWD) is the least common but the most severe form of a disease, with a prevalence of about 0. 5 to 1 per million in Western countries. The prevalence of type 3 VWD in the developing countries, with a high degree of consanguinity, is about 6 per million. Moreover, due to underdiagnosis of the milder cases, the prevalence of type 3 VWD is about 50% of the cases. Rarely, some patients develop the Von Willebrand Factor (VWF) inhibitors, which may subsequently develop severe anaphylactic reactions on further exposure to the VWF containing factor replacement therapy. The prevalence of inhibitor development in patients with type 3 VWD has been shown to be in the range of 5.8 to 9.5%. In the absence of a gold standard assay for the quantitation of VWF inhibitors, a correct diagnosis and management of these patients are often challenging. Objectives: The objective of this study is to standardize the Bethesda assay for the VWF inhibitors and to estimate the VWD inhibitor titer in two cases of congenital type 3 VWD, which developed the VWF inhibitors. Results and Conclusions: We could successfully standardize the Bethesda assay for the quantitation of VWF inhibitors in two patients with congenital type 3 VWD with inhibitors.